Salisbury Cathedral
Cloisters, which were an essential part of monastic life for exercise and meditation, were also built for show by the secular chapters of cathedrals. At Salisbury, the cloisters are the largest in England, and their geometric, traceried openings are among the best examples of this controlled use of structure, which marks another stage in the development of Gothic.